2023
DOI: 10.3390/ma16041381
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Bio-Based Silicone Coatings with Anti-adhesive Properties

Abstract: Hybrid polysiloxanes and polysilsesquioxanes grafted with naturally occurring bioactive phytochemicals: eugenol and linalool, were synthesized and investigated with regard to their structure and properties. The two series of materials, differing in the type of inorganic structure and the content of active groups, were coated onto the surface of glass plates, and their antibiofilm activities against bacteria Aeromonas hydrophila were assessed by luminometry and fluorescence microscopy. Bioactivity was correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
(81 reference statements)
0
0
0
Order By: Relevance
“…The same behavior was observed in PR12. However, Nowacka M. et al 53 have previously demonstrated the coupling between PDMS and triethoxysilanes with organic compounds (OC) based on the shift towards upfield of the Si–O (M) and O–Si–O (D) units in the 29 Si NMR spectrum. We observed a similar behavior in our 29 Si NMR spectra (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The same behavior was observed in PR12. However, Nowacka M. et al 53 have previously demonstrated the coupling between PDMS and triethoxysilanes with organic compounds (OC) based on the shift towards upfield of the Si–O (M) and O–Si–O (D) units in the 29 Si NMR spectrum. We observed a similar behavior in our 29 Si NMR spectra (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial and antibiofilm properties of superhydrophobic silicone coatings were derived as a result of the synergistic effects of the active components used (e.g., a composite of MOF, triclosan, epoxy resin, and polydimethylsiloxane [40]). Recently, our group has implemented a novel approach for modification of silicones with specific organic groups, including grafting polysiloxane backbones with naturally occurring bioactive phytochemicals: N-acetylcysteine [41,42], eugenol, and linalool [43] as well as polar but not ionic 2-(carboxymethylthioethyl)-, 2-(npropylamidomethylthioethyl)-, and 2-(mercaptoethylamidomethylthioethyl)-groups [44]. We have shown that the specific functionalization of polysiloxanes may increase their antiadhesive properties against a range of prokaryotic and eukaryotic microorganisms of different cell organization and cell wall structures, irrespective of the properties (hydrophobicity or hydrophilicity) of silicone materials.…”
Section: Antimicrobial Properties Of Polymeric Materialsmentioning
confidence: 99%